2002
DOI: 10.1175/1520-0442(2002)015<0353:tivoss>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Toward Improved Validation of Satellite Sea Surface Skin Temperature Measurements for Climate Research

Abstract: A poor validation strategy will compromise the quality of satellite-derived sea surface temperature (SST) products because confidence limits cannot be quantified. This paper addresses the question of how to provide the best operational strategy to validate satellite-derived skin sea surface temperature (SST skin ) measurements. High quality in situ observations obtained using different state-of-the-art infrared radiometer systems are used to characterize the relationship between the SST skin , the subsurface S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
583
2
11

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 581 publications
(633 citation statements)
references
References 44 publications
37
583
2
11
Order By: Relevance
“…At-sea measurements, of the skin surface temperature are usually lower than the temperature of the underlying water (cool skin effect), showing a dependence on wind speed (Fairall et al, 1996a;Minnett et al, 2011), and similar differences have been observed in freshwater environments (Cardenas et al, 2008). A warm near-surface layer can also appear on calm and sunny 30 days, without necessarily excluding the presence of a cool skin (Donlon et al, 1999). Under such conditions the thermal gradient can attain several degrees in the upper few meters of the water column (Ward, 2006).…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…At-sea measurements, of the skin surface temperature are usually lower than the temperature of the underlying water (cool skin effect), showing a dependence on wind speed (Fairall et al, 1996a;Minnett et al, 2011), and similar differences have been observed in freshwater environments (Cardenas et al, 2008). A warm near-surface layer can also appear on calm and sunny 30 days, without necessarily excluding the presence of a cool skin (Donlon et al, 1999). Under such conditions the thermal gradient can attain several degrees in the upper few meters of the water column (Ward, 2006).…”
Section: Introductionmentioning
confidence: 71%
“…Above 4 m s -1 , the two cases show a very similar behaviour, with average differences in cool skin effect and thickness of 0.002 ºC and 0.02 mm, respectively. For the higher wind speeds shear-induced turbulent heat exchange dominates, while for the lower wind speeds molecular and convective heat exchange 25 dominate (Fairall et al, 1996a;Donlon et al, 1999;Donlon et al, 2002). The simulated warm layer effect was more intense for the seawater case than for the freshwater case, especially for low wind speeds (Figure 4 b, d).…”
Section: Theoretical Salinity Effectsmentioning
confidence: 92%
See 3 more Smart Citations